Long-term stability of serum components in the Janus Serum Bank - Gislefoss, Randi E.; Grimsrud, Tom K.; Mørkrid, Lars (Scandinavian journal of clinical and laboratory investigation, 2008)
Objective. Biobank material is frequently used in epidemiological studies, but long-term storage of serum at −25°C may reduce the quality of the samples. Knowledge about the stability of components in biological samples is fundamental for the interpretation of such studies. Material and methods. We investigated the stability of seven biological components in serum samples stored at −25°C for 25 and 2 years compared with 1-month-old samples. Specimens from 130 blood donors from each group were randomly selected among men without a cancer diagnosis during the follow-up time. We compared the distribution, dispersion and localization of medians and means, and established reference intervals of the components. Results. The study demonstrated non-significant and numerically small differences in the levels of sodium, calcium, iron and creatinine over time. Differences between mean values for uric acid (−7.6%), potassium (+26.4%) and bilirubin (−59.4%) between fresh and 25-year-old samples indicated that sample handling before freezing and degradation during long-term storage may introduce a considerable bias for vulnerable components. Conclusions. There is large variation in level stability between different serum components in serum stored at −25°C. Differences in sample handling before freezing may introduce bias on vulnerable components. The present study supports a routine of careful matching of cases and controls on storage time in epidemiological studies when biobank material is used.